INTERNALIZING THE VALUES OF PANCASILA THROUGH THE KUDA KEPANG DANCE: A CONTEXTUAL AND CHARACTER-BASED LEARNING MODEL IN ELEMENTARY SCHOOLS - Nur Khayati; Rusnoto Susanto; Wachid Pratomo; Kristi Wardani Khayati (International Journal of Multidisciplinary Research and Literature, 2026)
Pancasila learning in elementary schools (SD) often faces challenges in the form of a conventional approach that is monotonous and focused solely on memorization of material. This results in weak internalization of Pancasila values ​​in students' daily lives. This article aims to disseminate ideas and practices for renewing Pancasila learning through the integration of a Project-Based Learning (PjBL) model based on local wisdom within the Merdeka Curriculum framework. This research uses a qualitative approach through literature review and analysis of good practices of Pancasila learning based on Project-Based Learning (PjBL) and local wisdom in elementary schools. Data were obtained from policy documents, journals, books, and related research results. The analysis was conducted using content analysis techniques, while data validity was maintained through source triangulation. The results of the study indicate that the reconstruction of Pancasila learning through a PjBL approach based on local wisdom is able to transform learning from a theoretical nature to a contextual, meaningful, and enjoyable one. Project-based activities provide space for students to explore the values ​​of mutual cooperation, social justice, and global diversity in a real-life manner. Through structured learning syntax, students not only understand Pancasila as knowledge (moral doing), but also feel it (moral feeling) and repeat it in real actions (moral action).